2022
DOI: 10.1038/s41598-022-11458-4
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatoid arthritis T cell and muscle oxidative metabolism associate with exercise-induced changes in cardiorespiratory fitness

Abstract: Rheumatoid arthritis (RA) T cells drive autoimmune features via metabolic reprogramming that reduces oxidative metabolism. Exercise training improves cardiorespiratory fitness (i.e., systemic oxidative metabolism) and thus may impact RA T cell oxidative metabolic function. In this pilot study of RA participants, we took advantage of heterogeneous responses to a high-intensity interval training (HIIT) exercise program to identify relationships between improvements in cardiorespiratory fitness with changes in pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 56 publications
0
3
0
1
Order By: Relevance
“… 26 Overall, cardiorespiratory fitness improvements were associated with positive changes in RA peripheral CD4+ T cell oxidative metabolism. 27 In sum, our previous findings highlight the potential for exercise training to impact clinical outcomes by targeting systemic and tissue‐specific metabolism, especially in older patients with RA. In the present study, we sought to further evaluate the effects of exercise, in combination with weight loss through diet modification, on cardiovascular health, disease activity, and patient‐reported outcomes in a population of patients with RA at high risk for cardiometabolic dysfunction.…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“… 26 Overall, cardiorespiratory fitness improvements were associated with positive changes in RA peripheral CD4+ T cell oxidative metabolism. 27 In sum, our previous findings highlight the potential for exercise training to impact clinical outcomes by targeting systemic and tissue‐specific metabolism, especially in older patients with RA. In the present study, we sought to further evaluate the effects of exercise, in combination with weight loss through diet modification, on cardiovascular health, disease activity, and patient‐reported outcomes in a population of patients with RA at high risk for cardiometabolic dysfunction.…”
Section: Introductionmentioning
confidence: 62%
“…In fact, improvements in RA disease activity were greatest in older age participants with high erythrocyte sedimentation rate (ESR), low cardiorespiratory fitness, and altered baseline skeletal muscle‐specific metabolism 26 . Overall, cardiorespiratory fitness improvements were associated with positive changes in RA peripheral CD4+ T cell oxidative metabolism 27 . In sum, our previous findings highlight the potential for exercise training to impact clinical outcomes by targeting systemic and tissue‐specific metabolism, especially in older patients with RA.…”
Section: Introductionmentioning
confidence: 76%
“…Decreased cardiorespiratory fitness [as measured by relative oxygen consumption (VO2) peak] is a strong predictor of CVD and overall mortality. Improvement in cardiorespiratory fitness in RA patients with high intensity interval training (HITT) was reported to be associated with increase in the amount of antiinflammatory cytokine IL-10 [185] and decrease in galectin-3, a marker of chronic inflammation and CVD risk [186]. A pilot study of 12 seropositive RA patients concluded that exercise induced improvements in the cardiorespiratory fitness and molecular markers of skeletal muscle oxidative metabolism were associated with changes in T cell metabolism which raises the question of whether exercise training, possibly through adaptations in skeletal muscle, can improve immune dysfunction [187].…”
Section: Ra and Exercisementioning
confidence: 99%
“…Оскільки зниження кардіореспіраторної витривалості є одним з найсильніших предикторів серцево-судинних захворювань та смертності від усіх причин, лікування РА вимагає розриву порочного кола, яке пов'язує відсутність фізичної активності з порушенням окисного метаболізму [2]. Так показано, що високоінтенсивні інтервальні тренування (ВІТ) -однохвилинні підходи високо-і низькоінтенсивних аеробних вправ, що чергуються, протягом 30 хвилин за сеанс три дні на тиждень протягом 10 тижнів -значно покращують кардіореспіраторну витривалість у хворих на РА в середньому на 19%.…”
unclassified